2000
DOI: 10.1017/s0003598x00059202
|View full text |Cite
|
Sign up to set email alerts
|

Metalworker or shaman: Early Bronze Age Upton Lovell G2a burial

Abstract: The Early Bronze Age barrow, Upton Lovell GZa,on Upton Lovell Down near the south westernedge of Salisbury Plain in Wiltshire, was one ofthe first to be investigated by William Cunnington(Cunnington 1806). His excavation in May 1802revealed an extended primary inhumation of astout male, accompanied near the feet by a largenumber of perforated bone points, three flint axesand a number of stones. These included fragmentsof a broken stone battle axe. At the chest was acomplete stone battle axe and a circular ston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 4 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…In other words, the construction of identity in archaeological contexts has long been explored through associations between material culture and individuals (in the case of craftspeople, for example, the identification of metalworkers on the basis of associations between people and suites of objects in mortuary contexts) (cf. Butler 1966;Shell 2000). Such analyses highlight a state, category or end point, rather than a process of 'becoming' or identity formation.…”
Section: Non-discursive Knowledge and The Construction Of Identitymentioning
confidence: 99%
“…In other words, the construction of identity in archaeological contexts has long been explored through associations between material culture and individuals (in the case of craftspeople, for example, the identification of metalworkers on the basis of associations between people and suites of objects in mortuary contexts) (cf. Butler 1966;Shell 2000). Such analyses highlight a state, category or end point, rather than a process of 'becoming' or identity formation.…”
Section: Non-discursive Knowledge and The Construction Of Identitymentioning
confidence: 99%
“…All we know is that they were suspended using another material, which resulted in rounding of the perforation edges. This may suggest that they served as decorations or dress elements, such as in the case of the Upton Lovell shaman's grave (Shell 2015).…”
Section: Function and Usementioning
confidence: 99%
“…From the outset, the literature has emphasised the 'primary male burial', with little attention to the other individual (e.g. Piggott 1962;Boutoille 2019;Shell 2000). Piggott (1962: 94) argued that the bone points and boars' tusks were part of a costume and that the burial dated to c. 1500 BC.…”
Section: Shaman Metalworker Goldworkermentioning
confidence: 99%
“…Piggott (1973) later compared the stone grave goods to metalworking tools from continental Europe, suggesting that the individual was a metalworker. Shell (2000: 271), highlighting that Thurnham (1870: 425f) had identified gold traces on one of the stone tools (STHEAD.2a), employed non-destructive, semi-quantitative X-ray fluorescence to analyse the traces, demonstrating that their elemental composition was similar to examples of Early Bronze Age gold. Shell concluded that the individual may have been a shaman, a metalworker, a goldworker, or possibly all three.…”
Section: Shaman Metalworker Goldworkermentioning
confidence: 99%